Pre-synaptic control of remote fear extinction in the neocortex - Vetere, Gisella; Restivo, Leonardo; Ammassari-Teule, Martine (Frontiers in Behavioral Neuroscience, 2012)
Consolidation of remote memory enhances immediate early genes induction (IEGs), augments the expression of the presynaptic growth associated protein 43 (GAP-43), and increases the density and size of dendritic spines in anterior cingulate (aCC) and infra-limbic (ILC) cortices. Remote memory extinction, however, does not uniformly alter consolidation-induced structural changes. In the aCC, the density, but not the size, of spines is reset to pseudo-conditioning levels while novel thin spines are formed in the ILC. Whether IEGs and GAP-43 also undergo region-specific changes upon remote memory extinction is undetermined. Here we confirm in the same batch of mice that c-Fos induction and GAP-43 expression are increased in both the aCC and the ILC 36 days after contextual fear conditioning. We then show that, in both regions, remote memory extinction is associated with decrease of c-Fos induction but no change in GAP-43 expression thus revealing similar, although protein-specific, pre-synaptic adaptations in aCC and ILC neurons. These observations, in addition to our previous report of region-specific post-synaptic structural changes, disclose a complex pattern of extinction-driven neocortical alterations suitable to support erasure or reinstatement of fear according to the environment demand.